TEATER SEBAGAI MEDIA EDUKASI DALAM MEMBENTUK KARAKTER SISWA DI SMPI AL-AZHAR 32 PADANG - Cindy Amalia Putri; Tulus Handra Kadir (Universitas Negeri Padang, 2025)
This research aims to determine the effectiveness of theatre activities as a means of fostering a spirit of mutual cooperation and collaboration among students, as well as to identify changes in the students' character in aspects of mutual cooperation and collaboration after being involved in theatre activities at SMPI Al-Azhar 32 Padang. This study employs a qualitative approach with descriptive analysis methods. The instrument used is the researcher themselves along with supporting tools such as writing materials and a camera. Data collection techniques include literature study, observation, interviews, and documentation. The steps used to analyze the data are data collection, data reduction, presentation of data, and drawing conclusions. The research findings indicate that Theatre as an Educational Medium in Shaping Student Character at SMPI Al-Azhar 32 Padang involved three activities: the Musical Drama Closing Performance of P5, the performance titled